Evaluation of polyurethane foam passive air sampler (PUF) as a tool for occupational PAH measurements - Strandberg, Bo; Julander, Anneli; Sjöström, Mattias; Lewné, Marie; Koca Akdeva, Hatice; Bigert, Carolina (Chemosphere (Oxford), 2018)
Routine monitoring of workplace exposure to polycyclic aromatic hydrocarbons (PAHs) is performed mainly via active sampling. However, active samplers have several drawbacks and, in some cases, may even be unusable. Polyurethane foam (PUF) as personal passive air samplers constitute good alternatives for PAH monitoring in occupational air (8 h). However, PUFs must be further tested to reliably yield detectable levels of PAHs in short exposure times (1–3 h) and under extreme occupational conditions. Therefore, we compared the personal exposure monitoring performance of a passive PUF sampler with that of an active air sampler and determined the corresponding uptake rates (Rs). These rates were then used to estimate the occupational exposure of firefighters and police forensic specialists to 32 PAHs. The work environments studied were heavily contaminated by PAHs with (for example) benzo(a)pyrene ranging from 0.2 to 56 ng m−3, as measured via active sampling. We show that, even after short exposure times, PUF can reliably accumulate both gaseous and particle-bound PAHs. The Rs-values are almost independent of variables such as the concentration and the wind speed. Therefore, by using the Rs-values (2.0–20 m3 day−1), the air concentrations can be estimated within a factor of two for gaseous PAHs and a factor of 10 for particulate PAHs. With very short sampling times (1 h), our method can serve as a (i) simple and user-friendly semi-quantitative screening tool for estimating and tracking point sources of PAH in micro-environments and (ii) complement to the traditional active pumping methods. •PUF can reliably and precisely accumulate PAHs after short exposure times (<1 h).•The PUF uptake rates (Rs) can be used to estimate the air concentrations of PAHs.•PUF works for semi-quantitative detection in high-exposure regions in workplaces.•Significant PAH contamination is revealed for the work environments considered.